Laparoscopic staging of borderline ovarian tumours – Technique and results - M, Klimatsouda; C, Donoudis; G, Kontopoulos; A, Daponte (Clinical Journal of Obstetrics and Gynecology, 2021)
Borderline Ovarian Tumors (BOT) tend to present more frequently nowadays, especially in younger women. Furthermore fertility preservation and laparoscopic management is often desired and therefore appropriate counselling is challenging and the treatment selection must be made on evidence based medicine. Adnexal mass could be a random finding when a typical gynecologic examination is performed. The diagnostic algorithm for possible BOT is the same as for any ovarian tumor, but the treatment options and techniques may vary based on patient’s willing to preserve her fertility or not. Laparoscopic or laparotomy approach has similar results although intraoperative findings and frozen section may redirect the primary treatment planning. When an initial conservative approach is chosen, a secondary approach including total hysterectomy and bilateral salpingo-oophorectomy with staging should be considered. Hence a full counselling is recommended before any primary approach.